Fourth imported rabies case since the eradication of rabies in Japan in 1957 - Nosaki, Yasunobu; Maeda, Kentaro; Watanabe, Maki; Yokoi, Takamasa; Iwai, Katsushige; Noguchi, Akira; Tobiume, Minoru; Satoh, Masaaki; Kaku, Yoshihiro; Sato, Yuko; Kato, Hirofumi; Okutani, Akiko; et al. (Journal of travel medicine, 2021)
A 32-year-old man, who visited Japan from the Philippines in 2020, was diagnosed with rabies, the first reported case in Japan since 2006. This is the fourth imported case of rabies since 1957; one case in 1970 was imported from Nepal and two in 2006 were imported from the Philippines.